2013
DOI: 10.4317/medoral.17970
|View full text |Cite
|
Sign up to set email alerts
|

Immunoexpression of α2-integrin and Hsp47 in hereditary gingival fibromatosis and gingival fibromatosis-associated dental abnormalities

Abstract: Objective: The purpose of the present study was to investigate the expression of the α2-integrin subunit and heat shock protein 47 (Hsp47) in two families with isolated gingival fibromatosis (GF) form and one family with GF associated with dental abnormalities and normal gingiva (NG). Study Design: Immunohistochemistry was performed with antibodies against α2-integrin and Hsp47 in specimens from two unrelated families with hereditary gingival fibromatosis (Families 1 and 2) and from one family with a gingival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Histopathological aspects observed in this study showed gingival tissues with a well-structured epithelium with elongated and thin papillae inserted into deep fibrous connective tissue with collagen fiber bundles running in all directions. These microscopic findings are similar to those observed previously in other families ( 15 , 16 ). Ultrastructural aspects revealed collagen fibrils presenting loops at their edges and loss of packing along with an apparent tortuous pattern of organization and dissociation of them.…”
Section: Discussionsupporting
confidence: 92%
“…Histopathological aspects observed in this study showed gingival tissues with a well-structured epithelium with elongated and thin papillae inserted into deep fibrous connective tissue with collagen fiber bundles running in all directions. These microscopic findings are similar to those observed previously in other families ( 15 , 16 ). Ultrastructural aspects revealed collagen fibrils presenting loops at their edges and loss of packing along with an apparent tortuous pattern of organization and dissociation of them.…”
Section: Discussionsupporting
confidence: 92%
“…In this regard, this study investigated ITGA2 and Hsp47 gene expression in active lesions and 7 days after root canal cleaning because several periapical cellular processes involve cell-extracellular matrix and cell-cell interactions (12). Integrins are critical components of the cell attachment machinery.…”
Section: Discussionmentioning
confidence: 99%
“…They are characteristically induced by stress signals such as elevated temperature, infectious agents, and inflammatory mediators participating in the folding and translocation of polypeptides across the cell membrane (11). Hsp47 is the major collagen-binding heat-inducible glycoprotein expressed in fibroblasts (12).…”
mentioning
confidence: 99%